PENGARUH PENGGUNAAN LITTER SEKAM, SERUTAN KAYU, DAN JERAMI PADI TERHADAP PERFORMA BROILER DI CLOSED HOUSE - Rohmatul Anwar; Khaira Nova; Tintin Kurtini (JURNAL ILMIAH PETERNAKAN TERPADU, 2014)
Using varians of litter such us rice hull, wood shavings, straw on keeping the broiler, can affectbroiler performance. Its happen because every single litter has different power of absorbing the water.Closed house is closed cage that build for making a better environment inside the cage. The aim of theresearch was to : (1) Knowing the effect of litter of broiler performance, and (2) Finding the bes tlitterfor broiler performance on the closed house.It was conducted during 26 days since April 14, 2014 to Mei 10, 2015 at the PT Ramajayafarm’s on Krawangsari village, sub District Natar, South Lampung District. The chiken used wasbroiler strain cobb with trademark CP 707 product by PT. Chareon pokphand Indonesia tbk for 270chiken. Broiler start to get handling between age of 14 and 26 days.The research method was experimentally with Completely Randomized Design (CRD) weredivided into 3 step and repeated for 6 times, that is p1: rice hull; p2 : wood shavings; p3 : straw. Thedata were analysis with Analysis of Variance and if it shows 5%, then the analyze would be continuedto Ducan test.The result indicated that the treatmentis : (1) The effect of litter from rice hull, wood shavings,straw did not have significant effect (P>0,05) on performance (consumption, body weight gain, feedconversion and income over feed cost) broiler at closed house. (2) The effect varians of litter (ricehull, wood shavings, straw) at closed house having the same effect as consumption, body weight gain,feed conversion and income over feed cost (IOFC) for broiler finisher phase